2022
DOI: 10.31219/osf.io/5d8kc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smartphone Photoplethysmography Covaries with Stress and Anxiety During a Digital Acute Social Stressor Preprint

Abstract: Heart rate is a transdiagnostic marker of affective states and the stress diathesis model of health. While most psychophysiological research has been conducted in laboratory environments, recent technological advances have provided the opportunity to index heart rate dynamics in real world environments with commercially available mobile health (mHealth) and wearable photoplethysmography (PPG) sensors that allow for improved ecologically validity of psychophysiological research. Unfortunately, adoption of weara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The overall scope of the current special issue of Psychosomatic Medicine is on “The Impact of Technological Innovation on Biobehavioral and Psychosomatic Medicine.” A comprehensive overview of technological innovations is provided with the goal that these and related innovations will be incorporated into research and clinical practice. The articles in this issue address the following general topics: the use of biological and behavioral sensors that are linked to user smartphones (8–13), the use of technology in clinical settings and issues related to VHs in clinical settings (14,15), digital mental health interventions (16,17), and the importance of reducing health disparities in technological development and implementation of technological innovation (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall scope of the current special issue of Psychosomatic Medicine is on “The Impact of Technological Innovation on Biobehavioral and Psychosomatic Medicine.” A comprehensive overview of technological innovations is provided with the goal that these and related innovations will be incorporated into research and clinical practice. The articles in this issue address the following general topics: the use of biological and behavioral sensors that are linked to user smartphones (8–13), the use of technology in clinical settings and issues related to VHs in clinical settings (14,15), digital mental health interventions (16,17), and the importance of reducing health disparities in technological development and implementation of technological innovation (18).…”
Section: Introductionmentioning
confidence: 99%
“…In this special issue, Van Dijk et al (8) demonstrated that photoplethysmography (using a smartphone’s camera) can be used to generate biofeedback of heart rate variability for reducing stress and anxiety among a cohort of 57 healthy volunteers as well as a traditional electrocardiogram-based heart rate variability biofeedback training in the laboratory. Nelson et al (9) conducted a proof-of-concept study that used photoplethysmography and a smartphone app to measure heart rate and then successfully correlate increases in heart rate to increases in perceived stress and anxiety among college students (using a modified version of the Trier Social Stress Test). In a study of approximately 32,000 adults, Mak et al (10) used an app-based optic sensor to measure both heart rate and blood pressure, which was then linked with ecological momentary assessments of acute and chronic levels of perceived stress.…”
Section: Introductionmentioning
confidence: 99%